Model Pendampingan Parenting Islami Bagi Ibu yang Ditinggal Suami Merantau dalam Membangun Keluarga Sakinah di Dusun Gayam, Mojopuro, Wonogiri - Rohmah, Syifa Nur; Rahmayani, Putri Nur Azizah; Fadila, Sekar Alifah Binar; N, Nasichah (Yayasan Daarul Huda Kruengmane, 2025)
This community service program was designed to strengthen the understanding of mothers in Dusun Gayam regarding Islamic parenting principles as an essential foundation for building a harmonious (sakinah) family, especially in households where the husbands work away from home. The seminar, titled “Mothers as the First School: Understanding Parenting Styles and Their Influence on Child Development,” was held on September 12, 2025, at Pos PAUD Kartika Siwi and attended by housewives who largely carry dual roles in childcare. The program employed several approaches, including material presentations, interactive discussions, and direct observations to assess participants’ learning outcomes. The findings indicate an improvement in participants’ understanding of Islamic parenting concepts, various parenting styles, and the importance of balancing affection with discipline. The mothers demonstrated positive changes in their perspectives and emotional readiness as primary educators of their children. Additionally, this activity succeeded in fostering a collective awareness of the importance of faith-based and ethical parenting in maintaining family harmony during the husbands’ absence.